Penggunaan Asesmen Jurnal Dalam Pembelajaran Kooperatif Untuk Menumbuhkembangkan Kemampuan Literasi Matematika Siswa di Bantaeng - Haeriyanti, Andi (Journal of Educational Science and Technology (EST), 2017)
The purpose of this research is to develop the ability of students' mathematical literacy by applying the journal assessment for students of MTs Negeri Gantarang of Bantaeng Regency. Method This research is qualitative research classroom action research. Data collection in research consists of 2 cycles with the intention to know the effect of journal writing on improving students' mathematical literacy skills. Each cycle consists of 4 stages of planning, implementation, observation, reflection. The result of the research showed that the ability of students' mathematics literacy VII A MTs Negeri Gantarang Bantaeng Regency through the use of journals as an alternative assessment in learning has grown and developed which is marked by the increase in formulating, applying and interpreting problems or problems given in LKS, Mathematical reasoning and using concepts, procedures, and facts to describe or explain in writing events or understandings during learning, seen from the results of student journal writing at the beginning of the journals have shown how students answer questions in the student worksheet and they can identify information and complete problem. It is also shown from the completeness of learning mathematics class VII A students have achieved the classical 76.19% or more than 75% of students who achieve a minimum score of 75